Exploring the Chatbot usage intention-A mediating role of Chatbot initial trust - Jyothsna M; Venkata Subbaiah P; Natalia Kryvinska (Heliyon, 2024)
Chatbots, an integral part of Digitalization, are becoming the cornerstone of modern-day marketing practices. This study's main objective is to identify the Chabot traits that have a bearing on users' confidence, acceptability, and engagement. Chatbots hold much potential for customer support in terms of service efficiency, cost savings, and customer experience. In addition to saving business costs, chatbots improve customer engagement, by reducing time and effort they need to spend in doing their business transactions. Aspiring, well-educated, and tech-savvy Gen Z customers perceive chatbots as highly compatible with their preferred method of seeking product-related information. As chatbots play a significant role in the marketing process, this study aims to identify the chatbot traits that influence customers' confidence, acceptance, and engagement with chatbots. Using the PLS-SEM tool/technique we computed a structural equation measurement model to test the traits leading to Chabot trust. The study also found that perceived ease of use, performance expectations, and social influence of chatbots are all greatly enhanced by trust on the part of the customers. Detailed statistical analysis showed that the trust that consumers have in chatbots strongly influences consumers' intentions, loyalty, and engagement levels. While gender had no impact on consumer intentions to use chatbots, the age of the respondents played a substantial role in their plans to use chatbots.